Our man in Malaya John Davis, CBE, DSO, Force 136 SOE and Post-War Counter-Insurgency - Shennan, Margaret (Monsoon Books, 2014)
When the Japanese invaded Malaya during World War II it seemed that John Davis' service in the country had come to an end. But nothing could have been further from the truth. Davis switched from the Federated Malay States Police to the Intelligence world; first with MI6 and then with SOE. Margaret Shennan tells the extraordinary, untold story of this courageous hero of the Second World War who planned the infiltration of Chinese intelligence agents and British officers into the Malayan peninsula. Yet Davis was more than a wartime hero. A fluent Cantonese speaker, he became an iconic figure in Malaya's colonial history, playing a fundamental part in its post-war history, when during the Communist Emergency he confronted Chin Peng, leader of the Communist Party, and witnessed the country's emergence as an independent nation state. Margaret Shennan uncovers the radical and temperamental man whose propensity to challenge the decisions of his superior officers did not always make him an easy comrade, but whose courage and determination to get the job done won him loyalty and respect. Illustrated with Davis' personal photographs, this is a story which truly deserves to be told.